Mapping digital information security management in the university libraries of Pakistan. Issue 1 (18th October 2019) - Aslam, Maria; Khalid, Ayesha; Batool, Syeda Hina; Farid, Ghulam
ABSTRACT: Maintaining digital information and protecting data assets remains a principal concern in libraries. Digital information security awareness is a major tool in overcoming incidents about data loss in libraries. This paper focuses on the awareness level of librarians and current status of digital information security management (DISM) in academic libraries of Lahore, Pakistan. The results also highlight the policies at individual or institutional level about DISM in selected libraries. The data were collected through structured interviews from 15 public and private sector academic librarians. Findings revealed that presently, digital resources are the integral part of university libraries such as OPAC's, official records and digital resources. However, information professionals did not show interest in security management of digital resources, as they least considered this role as part of their jobs. Therefore, they attended limited training programs to update their knowledge. A general trend indicates that institutional information technology departments were responsible for maintaining library server, network and hardware.